Decolonizing Disability Through Activist Art - Rice, Carla; Dion, Susan D.; Chandler, Eliza (Disability Studies Quarterly, 2021)
This paper mobilizes activist art at the intersections of disability, non-normativity, and Indigeneity to think through ways of decolonizing and indigenizing understandings of disability. We present and analyze artwork produced by Vanessa Dion Fletcher, the first Indigenous disability-identified Artist-in-Residence for Bodies in Translation (BIT), a research project that uses a decolonized, cripped lens to cultivate disabled, D/deaf, fat, Mad, and aging arts on the lands currently known as Canada. We begin by setting the context, outlining why disentangling the disability, non-normativity, and Indigeneity knot is a necessary and urgent project for disability studies and activisms. Drawing on Indigenous ontologies of relationality, we present a methodological guide for our reading of Dion Fletcher's work. We take this approach from her installation piece Relationship or Transaction?, which, we argue, foregrounds the need for white settlers to turn a critical gaze on transactional concepts of relationship as integral to a decolonized and an indigenized analysis of disability and non-normative arts. We then centre three original pieces created by Dion Fletcher to surface some of the intricacies of the Indigeneity/disability/non-normativity nexus that complicate recent discussions about recuperating Indigenous concepts of bodymind differences across white supremist settler colonial regimes on Turtle Island (North America) that seek to debilitate Indigenous bodies and lives. We intervene in these debates with reflections on what might be created—and what we might learn—when the categories of Indigeneity and (Western conceptions of) disability and non-normativity are understood as contiguous, particularly focusing on meaning-making within Dion Fletcher's developing oeuvre.